2010
DOI: 10.1111/j.1476-5381.2009.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexrazoxane protects the heart from acute doxorubicin‐induced QT prolongation: a key role forIKs

Abstract: Introduction: Doxorubicin, an anthracycline widely used in the treatment of a broad range of tumours, causes acute QT prolongation. Dexrazoxane has been shown to prevent the QT prolongation induced by another anthracycline, epirubicin, but has not yet been reported to prevent that induced by doxorubicin. Thus, the present study was designed to test whether the acute QT effects induced by doxorubicin could be blocked by dexrazoxane and to explore the mechanism. Results were compared with those obtained with a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 29 publications
4
41
1
Order By: Relevance
“…The results of the present study are in agreement with Xu [21] who showed weight loss, [22] who demonstrated significant reduction in systolic blood pressure [23] Different cellular mechanisms may explain doxorubicin-induced cardiac toxicity as increase intracellular iron accumulation causing increased oxidative stress [29], preventing the repair of damaged DNA strands [30], changes in vascular endothelium-derived vasoactive mediators (endothelin-1 and cardiac nitric oxide) [31] and alteration of cardiac-specific gene expression including struc tural, metabolic and enzyme activities [32].…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study are in agreement with Xu [21] who showed weight loss, [22] who demonstrated significant reduction in systolic blood pressure [23] Different cellular mechanisms may explain doxorubicin-induced cardiac toxicity as increase intracellular iron accumulation causing increased oxidative stress [29], preventing the repair of damaged DNA strands [30], changes in vascular endothelium-derived vasoactive mediators (endothelin-1 and cardiac nitric oxide) [31] and alteration of cardiac-specific gene expression including struc tural, metabolic and enzyme activities [32].…”
Section: Discussionsupporting
confidence: 81%
“…61 In addition, recent studies demonstrated the bioavailability of grape seed proanthocyanidins to the target organs exhibiting a superior protection against oxidative DNA damage and oxidative stress relative to vitamin C, E and β-carotene. 12 In support of our findings, it has been reported that various chemical compounds such as carvedilol, 62 rosmarinic acid, 63 dexrazoxane 64,65 as well as herbal agents including GSE, 18,39 saffron extract 66 and garlic extract 67 found to potentially be protective against DOX-induced cardiotoxicity. Based on reported studies GSE produces protective effect by several mechanisms including antioxidant effect, 68,69 decreasing the number of apoptotic cells, 70 prevention of DNA fragmentation, 15,71 regulation of the expression levels of the pro-apoptotic protein Bax-alpha, 72 increasing antiapoptotic protein Bcl-2 73 and inhibition of apoptotic signaling pathways.…”
Section: Cardioprotective Effect Of Grape Seed Extractsupporting
confidence: 75%
“…Doxorubicin and its metabolites can disrupt the Fe-S cluster of cytoplasmic aconitase and inhibit IRP-1, whose role it is to adapt the levels of cellular iron appropriate to the metabolic needs of the cell. It has been suggested that doxorubicin-mediated intracellular iron accumulation causing increased oxidative stress is a major aspect of doxorubicin toxicity and that iron chelators are highly effective in reducing doxorubicin-induced cardiotoxicity [13,14]. Interestingly, patients harboring gene mutations in hereditary hemochromatosis (HH) show increased susceptibility to doxorubicin cardiotoxicity and exacerbated iron metabolism [15].…”
Section: Doxorubicin-related Iron and Redox Injurymentioning
confidence: 99%
“…Of note, dexrazoxane appears to provide long-term cardioprotection without compromising oncological efficacy in doxorubicin-treated children [138]. The underlying mechanisms include iron chelation [11,14,139], protecting the heart from acute doxorubicin-induced QT prolongation via I(Ks) [13], and upregulation of Akt and Erk phosphorylation pathways [14].…”
Section: Preventionmentioning
confidence: 99%